PENGARUH MOTIVASI KERJA DAN SISTEM INFORMASI MANAJEMEN TERHADAP KINERJA PEGAWAI PADA BPJS (BADAN PENYELENGGARA JAMINAN SOSIAL) KETENAGAKERJAAN CABANG MEDAN - Dearma Sariani Sinaga; Julhendri Sinaga; Reza Simangunsong (Lembaga Penelitian dan Pengabdian Masyarakat Universitass Darma Agung, 2020)
This study aims at finding the effect of work motivation and Management Information Systems (SIM) on employee performance at BPJS (Social Security Organizing Agency) Medan Branch Employment. Quantitative research is used in this study. The population of this research is all employees of BPJS (Social Security Organizing Agency) Medan Branch Employment with a sample of 60 employees. The analytical method used in this study is the normality test, the multiple regression analysis test and the hypothesis test. T test results of work motivation variable tcount > ttable (4.683> 2.010) and sig value < 0.05 (0.000 < 0.05), it can be concluded that work motivation variable is partially significant and positive to support employee performance. On the value of management information system variables count > t table (4,727 > 2,010) and sig value> 0,05 (0,000 > 0,05), so it can be concluded that the Management Information System variable partially has a significant and positive effect on Employee Performance. In the F test results Obtained F value of 77.754 > F table 2.79 with a significance of 0.000 <0.05 because the regression model variable Work Motivation (X1) and Management Information Systems (X2) together related to Employee Performance variables (Y). Based on the analysis of the coefficient of determination can be seen in the value of R Square of 0.722 or 72.2% of employee performance variables of 27.8% needed by other factors outside this research variables such as work variables, personal factors, leadership style.